Application of fluorescent dye substrates for functional characterization of ABC multidrug transporters at a single cell level. Issue 9 (7th September 2016) - Nerada, Zsuzsanna; Hegyi, Zoltán; Szepesi, Áron; Tóth, Szilárd; Hegedüs, Csilla; Várady, György; Matula, Zsolt; Homolya, László; Sarkadi, Balázs; Telbisz, Ágnes
Abstract: ABC multidrug transporters are key players in cancer multidrug resistance and in determining the ADME‐Tox properties of drugs and xenobiotics. The most sensitive and specific detection of these transporters is based on functional assays. Assessment of the transporter‐dependent reduction of cellular uptake of the fluorescent dyes, such as Hoechst 33342 (Ho) and more recently DyeCycle Violet (DCV), have been widely advocated for the characterization of both ABCB1 and ABCG2 multidrug transporters. Detailed comparison of these supravital DNA‐binding dyes revealed that DCV is less toxic to ABCG2‐ and ABCB1‐expressing cells than Ho. ATPase measurements imply that DCV and Ho are similarly handled by ABCB1, whereas ABCG2 seems to transport DVC more effectively. In addition, we have developed an image‐based high content microscopy screening method for simultaneous in situ measurement of the cellular activity and expression of the ABCG2 multidrug transporter. We demonstrated the applicability of this method for identifying ABCG2‐positive cells in heterogeneous cell population by a single dye uptake measurement. These results may promote multidrug transporter studies at a single cell level and allow the quantitative detection of clinically important drug‐resistant sub‐populations. © 2016 International Society for Advancement of Cytometry